UPAYA MENINGKATKAN DISIPLIN GURU DALAM KEHADIRAN MENGAJAR MELALUI PEMBERIAN TUGAS - Hamsil Hamsil (JURNAL PENDIDIKAN ROKANIA, 2017)
Based on the temporary observation inSDN 019 Rokan IV Koto, there are many teachers who come late to school, still lack of discipline in teaching attendance in class, teachers are still late to class. Sample in this research is teacher as many as 8 people. The type of research in this study is PTS. Data collection techniques were taken using an observation sheet. Based on the results of data processing and discussion, it can be concluded that teacher discipline in teaching attendance is obtained in the first cycle of 58% with good category and in second cycle increased to 79% with good category. This means that the assignment can Improve the Discipline of teachers in the presence of teaching at SDN 019 ROKAN IV KOTO saidsuccessful.